Policy Implementation for Sustainable Development in Colleges of Education: A Case Study of South Western Nigeria - SALAMI, Muideen Oladeji; ADEWUYI, Habeeb Omoponle (Center for Risk Management & Sustainability and RSF Press, 2026)
This qualitative case study investigates the implementation of sustainable development policies in colleges of education in South Western Nigeria, focusing on curriculum integration, infrastructure development, and community engagement. Data were gathered through semi-structured interviews with 12 academic staff and policy document analysis across six institutions. Findings indicate partial policy implementation, hindered by inadequate funding, limited staff awareness, and weak governance structures. Key themes include fragmented policy execution and insufficient stakeholder collaboration. The study proposes a context-specific policy implementation framework aligned with Sustainable Development Goal 4 (Quality Education), emphasizing enhanced funding, mandatory staff training, and structured community partnerships. This framework contributes theoretically by refining the Advocacy Coalition Framework for resource-constrained settings and practically by offering actionable strategies for policymakers to strengthen institutional practices, ensuring sustainable teacher education that supports Nigeria’s socio-economic development